Unveiling Urinary Incontinence: A Holistic Examination of Demographics, Risk Factors, and Pregnancy-Associated Dynamics : Unveiling Urinary Incontinence - Ismail, Ayesha; Bibi, Iqra; Jahan, Faryal (Pakistan Journal of Health Sciences, 2024)
The pervasiveness of urinary incontinence (UI) is very high in pregnant females due to various physiological changes during pregnancy. So, its global burden has increased to 41%. Objective: To determine the demographics, physical activity, family history and mode of delivery as possible factors responsible for UI among females during pregnancy. Methods: A cross-sectional observational study was conducted for one year in Rural Health Centres Kangra and Kot Najibullah, District Haripur, Khyber Pakhtunkhwa, Pakistan, from Dec 1 2022 to Nov 30, 2023, involving 311 women aged 25-45 years, examining UI. It encompasses demographic profiles, prevalent risk factors, and nuanced dimensions during pregnancy. The findings delineate the participants' demographic characteristics, showcasing an average middle age with indications of overweight status. Results: It highlights the multifaceted nature of UI by associating it with various comorbidities, notably emphasizing the prevalence of high blood pressure and diabetes mellitus. The detailed exploration of UI during pregnancy reveals the predominance of stress-based types and varying severity levels. Moreover, this study offers insights into the impact of pregnancy on UI, illustrating a notable increase post-pregnancy. Conclusions: The information related to UI and its associated factors contributes valuable knowledge to healthcare professionals and physicians. They can provide tailored interventions and supportive therapeutic strategies to the individuals affected by UI and its etiological factors.